The effect of concrete quality on earthquake design: economical aspects - Akakın, Tümer. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2001., 2001)
There is a great advance in maximum concrete compressive strengths reached throughout years. So, today we have a large variety of concrete classes that can be produced by the concrete industry. But, the use of higher strength concrete would lower the cost of the building is a question. There are investigations done on the optimization of columns. But these optimizations have the lack of artificial limitations set by the codes. A numerical investigation is done on the use of different concrete classes according to Turkish Standards and Earthquake Codes. The investigation combinations includes three different story heights, four different concrete classes and First and Second Earthquake Regions. The costs of combinations are analyzed and compared. A market design computer program is used and its results are compared with a structural modeling computer program.
Keywords: Earthquake engineering.; Buildings -- Earthquake effects.; Concrete construction.